Analysis of Performance Results Reporting at the Personnel and Human Resource Development Agency: JEL Classification: M12, M54, J24, D23, J53 - Israwati, Ita; Sawaji, Jamaluddin; Arif, Muhammad Ridwan (Newinera Publisher, 2025)
This study aims to analyze the performance reporting mechanism and identify obstacles causing delays in the reporting process at the Nunukan Regency Personnel and Human Resources Development Agency (BKPSDM). Performance reporting, particularly the Government Agency Performance Report (LKJIP), is a crucial instrument for assessing the achievement of an organization's strategic goals and ensuring the effective implementation of the principles of public accountability and transparency. This research was conducted at the Human Resources Development and Personnel Agency (BKPSDM) of Nunukan Regency. This study used a descriptive qualitative approach, collecting data through in-depth interviews, observation, and documentation. The results indicate that the reporting mechanism has a clear basic structure, but it is not yet fully operational due to weak coordination, limited digital systems, and a lack of technical guidance. Meanwhile, reporting delays are also influenced by high operational workloads and the lack of standardized procedures. This research provides strategic recommendations in the form of strengthening the coordination system, developing reporting SOPs, increasing human resource capacity, and digitizing the reporting process as steps to improve the effectiveness and timeliness of LKJIP preparation in the future.